(untitled) (London Journal of Research In Management & Business, 2024)
In a context of globalization and increased competition, must navigate in increasing decision-making complexity. The emergence of big data offers a revolutionary opportunity by enabling unprecedented collection and analysis of information. This research explores how big data influences decision-making performance by examining their impact on the accuracy and relevance of decisions, as well as the reduction in the time needed to make them. The research includes a review of the literature, the presentation of a theoretical framework, the methodology used and a results analysis to provide practical and theoretic recommendations on the use of big data in decision-making.